Prognostic significance of C-reactive protein in patients with cervical cancer: a meta-analysis - Yang, Sheng; Zhang, Zongxin; Shen, Linglong (Frontiers in Oncology, 2023)
Background: Numerous studies have investigated the significance of pretreatment C-reactive protein (CRP) levels for determining the prognosis of cervical cancer (CC). The results of these studies, however, have been inconsistent. The present meta-analysis, therefore, focused on identifying the exact relationship of CRP levels with CC prognoses. Methods: We searched the following databases from their inception until April 18, 2023: PubMed; Web of Science; Embase; and Cochrane Library. From the search results, we estimated the significance of CRP levels in determining the prognosis of CC, based on combined hazard ratios (HRs) and relevant 95% confidence intervals (CIs). Results: The present meta-analysis included 12 studies, encompassing 2,204 patients. Based on combined data, an increased CRP level was significantly related to an unfavorable overall survival (OS) of patients with CC (HR = 1.63; 95% CI = 1.36–1.95; P < 0.001). Moreover, an increased CRP level was significantly associated with shortened progression-free survival (PFS) in patients with CC (HR = 1.68; 95% CI = 1.39–2.03; P < 0.001). According to the subgroup and sensitivity analyses, CRP level was a reliable factor in determining CC prognoses. Conclusions: Based on the results of our present analyses, increased CRP levels were significant predictors of poor OS and PFS in patients with CC. CRP level, therefore, could be an independent and inexpensive factor for determining the prognosis of patients with CC in clinical settings.